2015
DOI: 10.1186/s13054-014-0686-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal life support as bridge to lung transplantation: a systematic review

Abstract: IntroductionPatients with acute respiratory failure requiring respiratory support with invasive mechanical ventilation while awaiting lung transplantation are at a high risk of death. Extracorporeal membrane oxygenation (ECMO) has been proposed as an alternative bridging strategy to mechanical ventilation. The aim of this study was to assess the current evidence regarding how the ECMO bridge influences patients’ survival and length of hospital stay.MethodsWe performed a systematic review by searching PubMed, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 47 publications
(170 reference statements)
1
85
1
Order By: Relevance
“…transplantation, but with the improved safety profile of modern ECMO, several groups have demonstrated excellent outcomes with the use of pre-transplant extracorporeal support [27][28][29][30][31]. In some circumstances, VV ECMO via a dual lumen cannula can provide sufficient gas exchange to allow for the removal of mechanical ventilatory support for patients awaiting lung transplantation.…”
mentioning
confidence: 99%
“…transplantation, but with the improved safety profile of modern ECMO, several groups have demonstrated excellent outcomes with the use of pre-transplant extracorporeal support [27][28][29][30][31]. In some circumstances, VV ECMO via a dual lumen cannula can provide sufficient gas exchange to allow for the removal of mechanical ventilatory support for patients awaiting lung transplantation.…”
mentioning
confidence: 99%
“…More recent analyses using UNOS data from 2010 to 2015 showed that the adverse influence of ECMO was absent in high-volume lung transplant centers [61]. A systematic review including 14 retrospective studies pointed out that current data do not permit a definitive conclusion on the efficacy of ECMO as a bridge to transpla ntation [62]. However, these patients may have an acceptable 1-year survival [626364].…”
Section: Ecmo As a Bridge To Lung Transplantationmentioning
confidence: 99%
“…ECMO is a potentially life-saving therapy for patients with respiratory failure, 8789 and has been successfully used as a bridge to lung allotransplantation in highly-selected patients. 87,88,90,91 However, in most series posttransplant survival is inversely correlated to duration of ECMO support 87,88 and timely access to successful lung xenografts might substantially shorten the duration of ECMO support and improve outcomes.…”
Section: Tablementioning
confidence: 99%
“…87,88,90,91 However, in most series posttransplant survival is inversely correlated to duration of ECMO support 87,88 and timely access to successful lung xenografts might substantially shorten the duration of ECMO support and improve outcomes.…”
Section: Tablementioning
confidence: 99%